Concept Acquisition and Experiential Change - William S. Robinson (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
Many have held the Acquisition of Concepts Thesis (ACT) that concept acquisition can change perceptual experience. This paper explains the close relation of ACT to ADT, the thesis that acquisition of dispositions to quickly and reliably recognize a kind of thing can change perceptual experience. It then states a highly developed argument given by Siegel (2010) which, if successful, would offer strong support for ADT and indirect support for ACT. Examination of this argument, however, reveals difficulties that undermine its promise. Distinctions made in this examination help to clarify an alternative view that denies ADT and ACT while accepting that long exposure to a class of materials may induce changes in phenomenology that lie outside perceptual experience itself.
Keywords: acquisition of concepts; perceptual experience; hologram argument; ACT